Stimulasi Tumbuh Kembang Bayi Melalui Sosialisasi dan Simulasi Pijat Bayi pada Masyarakat di Puskesmas Tamalate Makassar: Stimulasi Tumbuh Kembang Bayi Melalui Sosialisasi dan Simulasi Pijat Bayi pada Masyarakat di Puskesmas Tamalate Makassar - Rika Riyandani; Riska Sabriana; Rosmiati Rosmiati; Lintje Tulu (Yayasan Ahmad Mansyur Nasirah, 2022)
Baby massage is one form of stimulation given to babies in an effort to stimulate more optimal growth and development. Baby massage can stimulate growth and development and a relaxing effect on babies if it is done in accordance with baby massage procedures and techniques and is done regularly, because it not only optimizes the development of children's movements, but also becomes a momentum to channel affection and attention and provide a relaxing effect. to the baby. improves blood circulation and respiration, stimulates digestive and excretory functions. increase weight gain. reduce depression and tension. sleep well. However, the right baby massage technique is not widely known by the public. A preliminary survey in the working area of the Tamalate Makassar Health Center found that almost all parents thought that baby massage was more likely to be done by a massage therapist. Parents do not know the further benefits of baby massage and do not understand how to massage the baby properly so that they do not do massage independently. The purpose of this community service is that it is hoped that parents can find out developmental stimulation according to the baby's age and how to do the right baby massage so that they have the awareness to stimulate their baby's development and carry out baby massage regularly. The target of this activity is parents who have toddlers aged 1-12 months in the working area of the Tamalate Makassar Health Center as many as 29 people. The method of activity used is lecture, discussion and simulation techniques or baby massage techniques. The results of the activity were all targets for attending counseling about developmental simulations and being able to do well-taught baby massage techniques and an increase in the level of participants' knowledge about developmental stimulation. It is hoped that parents can apply baby massage techniques regularly and independently at their respective homes according to the techniques that have been given.